DEVELOPING HOT-POTATOES BASED LISTENING MATERIALS FOR SECONDARY HIGH SCHOOL STUDENTS - Asih Sauramanda (ICoTE Proceedings)
This research in an ongoing research of devaloping hot-potatoes for listening materials It applied development reseach design and using analyze, design, and develop procedure, but this research has not reached the implementation and the evaluation stages and will be continued. This study started by designing the the drafts and developing the product. This product categorized into some levels, from the easiest to the difficult one. The students practice their  listening as well as play a game. In addition to play a game, students uncounsiously acquire new knowledge. The need for material that meets the educational standards is indispensable. Various publishers compete to publish books that can be sold and used in schools. Writing this article aims to inform the basics that can be applied in developing learning materials especially English learning. The influence of the principles of the development of learning materials should be used as a reference in designing and developing learning materials. Listening is one of the English language skills that should always be trained and improved so that students are accustomed to communicate in target language. With the listening material that can be used easily by students and teachers, it is expected that listening learning objectives can be achieved.